2019
DOI: 10.20473/jkl.v11i3.2019.252-258
|View full text |Cite
|
Sign up to set email alerts
|

Food Handlers Personal Hygiene in The Cafeteria of SDN Model and its impacts on Total Plate Count (TPC) in Food

Abstract: Canteen has an important role to provide of nutritious and safe food for students during school hours with relatively affordable prices. The results of Food and Drugs Monitoring (BPOM) inspection in 2013 by taking a sample of School Children Confectionary (PJAS) found that 80.79% of the samples confirmed as free from microbiological contamination. These results decrease in 2014, whereas PJAS samples confirmed as free from microbiological contamination is was 76.18%. This study aimed to analyze the implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…that food sold open can increase the risk of food contamination by the environment, both through the air, dust, vehicle fumes, and even insects. Food sold on the side of the road will be very easily exposed to dust and fumes from flying vehicles [9].…”
Section: Storage Of Foodstuffsmentioning
confidence: 99%
See 2 more Smart Citations
“…that food sold open can increase the risk of food contamination by the environment, both through the air, dust, vehicle fumes, and even insects. Food sold on the side of the road will be very easily exposed to dust and fumes from flying vehicles [9].…”
Section: Storage Of Foodstuffsmentioning
confidence: 99%
“…In line with the results of the interviews, the results of observations made on canteen owners showed the same thing where key informants were not found or obtained, namely canteen owners who had skin diseases, ulcers or ISPA, this is in line with research conducted by Muhammad Hakam Arifin and Yuni Wijayanti with the title Food Hygiene and Sanitation in Elementary School Canteens and Madrasah Ibtidaiyah 2019 that the results showed that the majority of respondents, namely 20 people met the requirements not to suffer from easily transmitted diseases such as coughs, colds, influenza, diarrhea, similar stomach. This can be seen from the majority of respondents who were not suffering from certain diseases that were easily transmitted while being observed and respondents who claimed not to work when they were sick [9].…”
Section: Suffering From Infectious Diseases Such As Skin Diseases Ulc...mentioning
confidence: 99%
See 1 more Smart Citation